Kebebasan Beragama di Era Digital; Analisis Wacana Teun A Van Dijk dalam Film “Bumi itu Bulat” - Robikah, Siti; Rizqo Faridatul Ulya (Journal of Religion and Film, 2023)
This article observes that everyone has the freedom to convey the message of freedom of religion and belief in the digital age. Not only through writing, everyone is also allowed to convey it in various ways. One of the interesting things for Indonesian people is through a movie. Through film, people will more easily accept the message of religious freedom than through writing. Many films about religious freedom have been shown in cinemas, one of which is a film entitled The Earth is Spherical. The film Bumi tu Bulat produced by Robert Ronny tells the story of the journey of the Rujak Accappella group. In the film Bumi, Bulat tells a lot about the religious problems faced by Indonesian society. About religious harmony that was later introduced by many radical beliefs and caused religious problems that later arose. Through the figure of Aisha, this film shows what religious life is like in Indonesia. Aisha is a singing artist who stopped singing due to migration. Then meet the members of Rujak Accappella whose members consist of various religions. In this study, the writer uses a qualitative approach using Teun A Van Dijk's discourse analysis theory. The writer tries to see three important components in the movie Bumi tu Bulat. That is text analysis, social cognition and social context contained in the film The Earth is Round. The filmmaker's global analysis in the film "Earth Is Round" conveys his message about the existence of the problem of religious intolerance in Indonesia. The writer found that the scenario of the movie "Earth Is Round" contains information related to facts, has an element of coherence in it, so that the sentence forms discourse and meaning. The presentation of words and sentences in the movie "Earth Is Round" displays a style of language that is easy to catch, understand and understand. Discourse analysis also provides information that the movie "Earth Is Round" describes the situation and the state of religion in Indonesia which is experiencing a crisis of tolerance. Keywords: Discourse analysis, film, religious freedom